the lion muse. - Bargen, Walter (Isotope)
This article compares the computer to a mountain lion. The author relates the story of a computer technician from Germany who is accused of killing, dismembering and eating a man who agreed to all of this over the Internet. The author also relates about a cybernetic poet program that enables a computer to write original poetry. According to the author, man has missed the mountain lion waiting to maul the gigabytes, devour the RAM. Eventually, man will be devoured by the machine he is grooming.